Challenges experienced by physically challenged learners in practical physical education classes in South Africa: a systematic analysis - Thekethe, Dikeledi B.; Ogbonnaya, Ijeoma C. (Noyam, 2024)
This paper, framed within the interpretivism theory, argued that government, stakeholders, and policymakers could foster and promote policy advocacy to address the challenges militating against the participation of physically challenged learners (PCLs) in practical physical education (PE) classes. Despite the noticeable need for physical activities in the lives of PCLs, there are growing concerns that learners in physical education classes still face many challenges in practical classes. The research was a systematic review of literature that identified studies that focused on the challenges that PCLs experience in practical physical education classes. Data was gathered from a collection of relevant articles as well as 20 publications that were critically reviewed. Only ten publications were found to meet the inclusion criteria. As a result, four main themes emerged from the data as thematic analysis was adopted. The findings revealed that PCLs frequently encounter challenges such as inaccessible equipment, poor social support, the PE curriculum/programme, and a lack of teachers training in practical physical education classes, which can limit their ability to engage and fully participate in PE practical classes. The study contributed to the body of physical education studies by providing a framework for a more integrated Physical Education for Physically Challenged Learners (PCLs), which could be implemented all around the world. It recommends, among others, that the members of the executive councils, school management teams and policymakers should work together by providing schools with accessible equipment and strong social support for PCLs to feel less isolated and more supported. This study concludes that exploring these challenges and developing coping strategies can help to ensure that PCLs can participate and benefit from PE practical classes.
Keywords: Physical education; physically challenged learners; practical classes; systematic analysis